Enhancing Cash Management and Financial Literacy in Small Coffee Shop Banda Aceh - Fitriningrum, Andriati; Ramadhan, Rizki; Pulungan , Andrey Hasiholan (Penerbit Goodwood, 2025)
Purpose: This community service initiative aims to assist Warung Kopi Pak Haji, a small-to medium-sized coffee establishment in Banda Aceh, by improving its cash management strategies and financial literacy competencies. Methodology: Project case assignments, mentoring, and lectures were chosen to allow participants to feel that they were part of the decision-making process for their day-to-day operations. Additionally, it allows participants to gain and enhance their understanding of handling cash and finances. Results: The coffee shop's unique characteristic, financial unpredictability, necessitates the development of skills in cash management and strategic planning to ensure daily operations and reduce uncertainties. Cocnclusion: This community service program demonstrates that enhancing financial literacy and cash management skills is crucial for the sustainability of small and medium-sized enterprises. Through training, mentoring, and project-based learning, the coffee shop staff and owner gained practical knowledge of managing daily operations, planning future investments, and reducing financial uncertainty. These outcomes highlight the importance of continuous capacity building to strengthen SMEs’ resilience and promote long-term growth. Limitations: Long business hours, participants’ work schedules, and capabilities make constant participation in training exceedingly difficult for all employees. Contribution: This community service supports the financial capacity, entrepreneurship, and skills of small and medium-sized businesses, particularly focusing on enhancing cash management effectiveness and financial literacy in a small-to-medium coffee shop in Banda Aceh. Managing finances effectively for daily operations is essential for the success of SMEs.